Impella RP support in refractory right ventricular failure complicating acute myocardial infarction with unsuccessful right coronary artery revascularization. (1st March 2020) - Gramegna, Mario; Beneduce, Alessandro; Bertoldi, Letizia F.; Pagnesi, Matteo; Marini, Claudia; Pazzanese, Vittorio; Camici, Paolo G.; Chieffo, Alaide; Pappalardo, Federico
Abstract: Background: Impella RP has been used to treat right ventricular failure (RVF) developing in various clinical settings that underlay different pathological mechanisms and lead to distinct prognostic implications. Methods: This is a single-centre retrospective study including all consecutive patients, from January 2015 to December 2018, with inferior STEMI due to acute thrombotic occlusion of right coronary artery (RCA) and unsuccessful primary percutaneous coronary intervention (PCI) complicated by refractory RVF managed with an Impella RP device. Results: A total of 5 patients have been treated. The mean age was 73 ± 9 years, 80% were males. All patients, except one, were hemodynamically stable at hospital admission. In all patients, PCI resulted unsuccessful (final TIMI flow < 3), with subsequent development of refractory RVF and cardiogenic shock in the catheterization laboratory, despite the use of inotropes and intra-aortic balloon pump (IABP). In 80% of the cases, Impella RP was placed immediately after PCI. Hemodynamics improved immediately after initiation of Impella RP support, with an increase in systolic blood pressure from 91 ± 17 to 136 ± 13 mmHg, a decrease in central venous pressure from 16 ± 2.5 to 12 ± 4 mmHg and a resolution in lactates from 4.5 ± 2.5 to 1.6 ± 0.7 mg/dL. Mean duration of IABP and Impella RP support were 4 and 7 days, respectively. RV recovery occurred in 80% of the cases. All patients survived at 30-day. Conclusions: In patients with AMI complicated by unsuccessful revascularization of RCA and refractory RVF, the use of Impella RP device resulted in immediate hemodynamic benefit with reversal of shock and favourable survival at 30-day. Highlights: This is the first study focused on Impella RP in acute myocardial infarction setting. Impella RP provides effective hemodynamic support. A proper patient selection and timing for Impella RP offer good clinical outcomes.